ASPECTOS DA VIOLÊNCIA DE GÊNERO CONTRA A MULHER NO CINEMA INTERNACIONAL - Ivy Correia Braga (TRF2, 2019)
The is an analysis of the international film industry addressing expressions of violence against women as a gender, accosting from the presence and exercising of a symbolic power, to the less-veiled violence found in pulp flics and mega productions from Hollywood alike. Focusing on symbolic violence as ways of domination derived from symbolic power, there comes the need of clarifying this violence works’ subtleties in media. The film industry was chosen as production of art and, therefore, reflection of a culture and society. The selected works comprehend a timeframe ranging from the late 80’s to the year of 2017, besides counting with a considerable variety of movie genres. More precisely, the movies “Tyranossaur” (2011), “The Cook, The Thief, His Wife & Her Lover” (1989), and “Phantom Thread” (2017) were analysed deeply and in isolation. The franchise “John Wick” (2014 and 2017) and the movie “Atomic Blonde” (2017) were comparatively analysed. The movies from the “007” saga (1995) will also be mentioned in brief analysis along this research.